Natural Resources of India - Planning Commission (Planning Commission Government of India, 1963)
The Natural Resources of India report provides a comprehensive assessment of the country's essential environmental assets, including land, water, energy, and minerals. It distinguishes between renewable resources such as soil, water, and biodiversity, and non-renewable resources like minerals. The Planning Commission, established in 1950, spearheads systematic evaluation and optimal utilization through surveys and strategic planning. Key findings include limited per capita cultivable land, significant surface and groundwater potential for irrigation, substantial coal and mineral reserves, and emerging energy options like nuclear, wind, and solar power. Effective management and conservation of these resources are emphasized as critical for economic growth, industrial development, employment generation, and sustainable socio-economic progress in India.
Government of India Planning Commission
Keywords: Natural Resources; Renewable Resources; Non-Renewable Resources; Land Resources; Water Resources; Energy Resources; Mineral Resources; Resource Management; Planning Commission; Sustainable Development